Renal Endometriosis in a Child - I.P. Zhurilo; A.Yu. Gunkin; P.A. Lepikhov; I.A. Starichenko (Zaslavsky O.Yu., 2012)
The problem of extragenital endometriosis was discussed in this article. We describe a rare case of renal endometriosis in 13-year-old child. Questions of diagnosis and therapeutic approach in this pathology were discussed.